Applied engineering sciences : proceedings of the 2014 AASRI International Conference on Applied Engineering Sciences, Hollywood, LA, USA - Deng, Wei, 1974-; AASRI International Conference on Applied Engineering Sciences (2014 : Los Angeles, California). (Leiden : CRC Press, 2015)
This proceedings volume contains selected papers presented at the 2014 AASRI International Conference on Applied Engineering Sciences, held in Hollywood, LA, USA. Contributions cover the latest developments and advances in the field of Applied Engineering Sciences.
ICAES 2014.
Includes bibliographical references and index.
Keywords: Engineering -- Congresses